UNDERSTANDING CHRISTIAN FUNDAMENTALISM THROUGH AMERICAN EVANGELICALISM - J. Rosario Narchison (Journal of Dharma, 1990)
The term "Fundamentalism" is of definite Christian origin. It was coined in the early part of the twentieth century in support of a particular Christian ideology and movement within American Protestantism. Christian Fundamentalism, meaning the concerted efforts of Chris- tian bodies to conserve the fundamental elements of their religion, is almost as old as Christianity itself. And in this sense the New Testament is the classical and the most ancient proof of Christian fundamentalism. Of later history, official Roman Catholicism represents the highly institutionalized and hierarchically centralized form of Christian fundamentalism.